PENGARUH PROFITABILITAS DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN SEKTOR FOOD & BEVERAGES PADA BEI PERIODE 2019 – 2022 - Sartiko, Binto; Sisilia, Arnetta; Amalia, Ivonne; Medianto, Andreas (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
The aim of this research is to analyze whether there is an influence of profitability (ROA)and debt policy (DER) on the value of food & beverages companies on the IDX for the 2019- 2022 period. The analysis technique used in this research is by using multiple linearregression analysis techniques using SPSS version 26 application. The sample in this studywas determined using a saturated sampling technique method so that there were 24companies in this study. The data used in this research is secondary data and datacollection techniques use documentation techniques. Hypothesis testing uses the t test andF test. Based on data analysis, the results show that profitability and debt policy do nothave a significant effect on company value. This is due to abnormalities in the data periodtaken which were caused by the Covid-19 outbreak.